UK UNIVERSITIES ARE WELCOMED TO JOIN APUCEN - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 25 March 2017 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Datuk Dr. Asma Ismail recently received a delegation from several United Kingdom (UK) universities to discuss potential cooperation in various fields of study and research.